(untitled) (Journal on studies and research of academic knowledge, 2008)
The objective of the present study is to analyse the processing of hospital waste from the Hospital Regional of Encarnación, and to investigate the different stages involved in the process including: generation, segregation, packaging, transport and internal storage, collection, transport and final deposition. Data collection techniques such as questionnaires, interview have been applied to the hospital employees, besides other information and observation in the place. According to the results of the investigation, is recommended to get a better internal segregation in the hospital, using the bags according to the current laws, so as well the previous treatment of harmful wastes before transporting them to the Municipal Landfill. Finally is confirmed the hypothesis that inadequate waste management constitutes a health risk for human beings, it contaminates the environment and does not adhere to legal requirements.